2012
DOI: 10.1093/protein/gzs035
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a new function in an esterase: simple amino acid substitutions enable the activity present in the larger paralog, BioH

Abstract: Gene duplication and divergence are essential processes for the evolution of new activities. Divergence may be gradual, involving simple amino acid residue substitutions, or drastic, such that larger structural elements are inserted, deleted or rearranged. Vast protein sequence comparisons, supported by some experimental evidence, argue that large structural modifications have been necessary for certain catalytic activities to evolve. However, it is not clear whether these activities could not have been attain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…2a). Expression of the P. aeruginosa in an E. coli ∆bioH strain resulted in robust growth in biotin-free medium as expected from prior studies with various nonorthologous esterases 24, 25, 30, 31 (data not shown). Alignments of the two BioH proteins argue that the two enzymes share the same esterase catalytic triad (Ser-His-Asp) (Fig.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…2a). Expression of the P. aeruginosa in an E. coli ∆bioH strain resulted in robust growth in biotin-free medium as expected from prior studies with various nonorthologous esterases 24, 25, 30, 31 (data not shown). Alignments of the two BioH proteins argue that the two enzymes share the same esterase catalytic triad (Ser-His-Asp) (Fig.…”
Section: Resultssupporting
confidence: 80%
“…The three BioH proteins with demonstrated pimeloyl-ACP methyl ester cleavage activity are given in large bold type. The PA3859 protein is included as the outlier since it is a P. aeruginosa α/β-hydrolase known to lack pimeloyl-ACP methyl ester cleavage activity 31 . The blue dotted box with the exception of PA3859 denotes the operon-encoded BioH proteins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations